2015
DOI: 10.1016/j.infrared.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Low bandgap mid-infrared thermophotovoltaic arrays based on InAs

Abstract: We demonstrate the first low bandgap thermophotovoltaic (TPV) arrays capable of operating with heat sources at temperatures as low as 345 o C, which is the lowest ever reported. The individual array elements are based on narrow band gap InAs/InAs 0.61 Sb 0.13 P 0.26 photodiode structures. External power conversion efficiency was measured to be ~3% from a single element at room temperature, using a black body at 950 o C. Both 25-element and 65-element arrays were fabricated and exhibited a TPV response at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…When concentrating the 800 °C radiation to about 4 W/ cm 2 at room temperature, the TPV efficiency increased to 1.3%, largely due to the 3 times increase in Voc. Using a 950 °C blackbody source with 720 mW/cm 2 power density as in our previous work, this InAs TPV achieved Jsc = 1.32 A/cm 2 at 300 K Tc, which is about 47% higher than the LPE grown InAs TPV with an InAsSbP window layer [13]. The power efficiency was estimated around 3.6%, which is also a little higher than our previously reported value.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…When concentrating the 800 °C radiation to about 4 W/ cm 2 at room temperature, the TPV efficiency increased to 1.3%, largely due to the 3 times increase in Voc. Using a 950 °C blackbody source with 720 mW/cm 2 power density as in our previous work, this InAs TPV achieved Jsc = 1.32 A/cm 2 at 300 K Tc, which is about 47% higher than the LPE grown InAs TPV with an InAsSbP window layer [13]. The power efficiency was estimated around 3.6%, which is also a little higher than our previously reported value.…”
Section: Resultsmentioning
confidence: 44%
“…However, until now, much less investigation has been carried out on InAs based TPVs compared with GaInAsSb and GaSb devices. Voc of ~0.06 V and Jsc of ~0.9 A/cm 2 have been obtained from InAs TPV cells illuminated by a 950 °C thermal source [13]. But relatively little information has been reported on the operating characteristics and potential of InAs TPVs.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the condenser section contributes to major energy losses as waste heat in the thermal power plant system, the temperature condition makes any recovery technologies impossible to be deployed. In particular, TPV system recorded the lowest possible heat source temperature of 345 ºC with InAs TPV cell [67]. Therefore, the studies concluded the huge potential for TPV implementation in thermal power plant which can be done at boiler and turbine section.…”
Section: B Tpv Implementation In Thermal Power Plantmentioning
confidence: 93%
“…The bandgap of InAs is about 0.35eV, the InAs TPV cells fabricated by the Zn diffusion method absorb the photons in the range of 1~3.5 m µ [5,[20][21][22][23],thus they have import applications in low temperature TPV systems. Figure 8a shows the Zn profiles in n-InAs under Ga-rich conditions.…”
Section: Zn Diffusion In Inasmentioning
confidence: 99%